THE RELATIONSHIP BETWEEN STUDENTS' COGNITIVE ACHIEVEMENT IN PAI SUBJECTS AND THEIR RELIGIOUS ATTITUDES AT SDN 90 CIBIRU PANYILEUKAN DISTRICT BANDUNG - Robaeah, Wilam Nafilah; Karman, Karman; Nasir, Tatang Muh; Turwanto, Teguh; Yulistiawati, Lilis (ATTA`DIB, 2023)
It cannot be denied, someone who has high religious knowledge is directly proportional to their high religious attitude, and vice versa. That is, to what extent they can accept the at-tainment of religious knowledge that they have to apply. This study aims to: 1) determine stu-dents' cognitive achievement in PAI subject in class VI SDN 90 Cibiru; 2) knowing the reli-gious attitudes of students in PAI subjects in class VI SDN 90 Cibiru; and 3) knowing the re-lationship between students' cognitive achievement in PAI subjects and their religious atti-tudes in class VI SDN 90 Cibiru . The approach used in this study is a quantitative approach to the correlative descriptive method. Analysis of the data used through statistical calcula-tions. Data collection techniques used were questionnaires, observations, documentation studies, literature studies, and interviews. The sample used was class VI students. Where sampling was used 10% -15% of the existing population, that is, from 257 populations, 30 samples were used. The results of the study show that: 1) based on the calculation of cogni-tive achievement of students, the price (81.99) is identified in the very good category; 2) The students' religious attitudes based on calculations obtained prices (3.58) identified in the high category; and 3) the relationship between students' cognitive achievement and their religious attitude through Spearman's rank correlation test obtained the correlation value (0.188) as-sumed to be in the very low relationship category, then compared with the price of ρ table (0.306) then Ho is accepted and Ha is rejected. Then determine the price of it with a: 5%. obtained the value of t count (1.01) and t table (1.697).